Rare, rapid and resolved: a case of primary aggressive testicular non-Hodgkin’s lymphoma - Doshi, Samit Himanshu; Kumar, Vikash; Gourabathini, Siva Prasad; Gajengi, Ajaykumar (International Surgery Journal, 2026)
Primary testicular lymphoma (PTL) is a rare and aggressive extra nodal manifestation of non-Hodgkin’s lymphoma (NHL), accounting for 1-2% of all NHL cases and 5% of testicular tumors. We report a case of a 62-year-old male presenting with a rapidly enlarging painless right testicular mass and right inguinal lymphadenopathy. Imaging and PET-CT revealed a metabolically active testicular mass with regional lymph node involvement. He underwent right high inguinal orchidectomy with inguinal lymph node excision. Histopathology and immunohistochemistry confirmed diffuse large B-cell lymphoma (DLBCL), non-germinal center type, double expressor phenotype. The patient received systemic R-CHOP chemotherapy with CNS prophylaxis and adjuvant radiotherapy. Follow-up PET-CT at 1 year showed complete remission. This case highlights the importance of a multimodal approach including surgery, immunochemotherapy, CNS prophylaxis, and scrotal irradiation for optimal disease control in PTL.